Using a Helicopter to Measure River Discharge under Extreme Environmental Conditions: A Methodological Approach on the Sagavanirktok River, Alaska - John Keech; Mike Terwilliger; Joel Bailey; Horacio Toniolo (Water, 2018)
River discharge is a critical variable in many aspects of hydrology, particularly river mechanics. Due to the importance of river discharge, the standards for performing measurements are already established. In the extreme environmental conditions of breakup in Arctic regions, field crews face significant challenges in carrying out measurements, including risks to personnel, equipment safety, and river access difficulties. The use of a helicopter in performing river discharge measurements with these challenges provides an alternative to using a boat. We present the details of measuring river discharge with the help of a helicopter along the braided Sagavanirktok River on the Alaska North Slope.